POSITIONING ISLAMIC LEGAL THEORY IN THE DEVELOPMENT OF ISLAMIC FINANCE - Qonita, Nuha (Fakultas Syariah, 2019)
Islamic finance continues to grow over the world, the development of technology plays a crucial role to support Islamic finance. The great innovation of technology may come to dig up the potential of Islamic financing, yet digital system needs for sharia compliance, both are in similar needs for sharia overviews regardless different opinions of ijtihad in this modern time. Emphasizing case by case of Islamic finance has been done by the sharia scholars in producing the new product of Islamic banking and financing. The Islamic jurisprudence however should consider the substence and maqasid form of sharia. The objective of this paper is to enlight some vital parts of Islamic legal theory as part of Islamic law in implementing sharia compliance. Furthermore, provide the role of legal system which takes a crucial place in implementing the system, it should be harmonized in the existing condition of Islamic finance. This paper is qualitative methods with deep analysis on Islamic legal theory among muslim scholars.